Natives' gender norms and the labor market integration of female immigrants - Julia Bredtmann; Sebastian Otten (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Using data from the European Social Survey 2002-2020 covering immigrants in 25 European countries, this paper investigates the role of natives' gender norms in the labor market integration of female immigrants. To analyze the role of natives' gender norms, we exploit intertemporal, interregional, and age-specific variation in female-to-male labor force participation ratios. We find a positive and robust association between immigrant women's labor supply and the femaleto-male labor force participation ratio in their region of residence. No similar association is found among immigrant men. We provide evidence that our finding is due to the cultural assimilation of female immigrants to native women's gender norms, and not the result of exposure to similar institutions and economic conditions. Based on a gravity model of female immigrants' regional location choice, we further provide supportive evidence that the association between natives' gender norms and immigrant women's labor supply is not driven by a selective location choice of female immigrants.
Keywords: J16; J22; J61; 330; Female labor force participation; immigration; gender norms